Assessing EFL Student Teachers’ Writing Skills through Reflective Journal - La Sunra; Sahril Sahril; Syarifah Farahdiba (Celebes Journal of Language Studies, 2021)
Writing has been claimed to be the last and hardest language skill to be learned by language learners, either native speakers of the language or foreign/second language learners. Within this respect, writing becomes a serious challenge for many EFL students to master their target language. EFL students use reflective journals as learning logs to express or capture their ideas to produce logical and meaningful writing. This study tried to investigate the EFL student teachers’ writing skill through their reflective journal written through Micro Teaching course in English Education program. Their writing skills were examined in terms of content, organization, vocabulary, language use, and mechanics applying the framework of Jacobs’ et al, (1981). The study used descriptive method to examine the EFL students’ writing skill through their reflective journals. The research findings showed that the EFL students’ writing skills through their reflective journal in micro teaching course were at good level. The data analysis also indicated that the EFL students performed the best in mechanics aspect and the lowest in vocabulary aspect.